DETERMINANTS OF LABOR DEMAND; EMPIRICAL EVIDENCE FROM EAST KALIMANTAN - Anwar, Syaiful (AFEBI Economic and Finance Review, 2018)
This study aims to examine the impact of revenue sharing of natural resource, capital expenditure realization from the government, gross fixed capital formation and length of roads on population 15 Years of age and over who worked as proxy Labor in East Kalimantan period 2001-2013. This study found that revenue-sharing funds have a positive and significant impact on the increase in the number of workers. The Effect of Capital Expenditure on the rise of manpower indicates a positive sign and significant on grwoth of labor. The Effects of Investment on Labor Improvement shows a positive and significant sign of direction. The influence of road infrastructure on the rise of manpower indicates the direction of the sign which is also positive and significant. JEL Classification: J20, J23, J24 Keywords: capital expenditure, labor, East Kalimantan, revenue sharing of natural resource